2017
DOI: 10.1016/j.neuron.2017.07.031
|View full text |Cite|
|
Sign up to set email alerts
|

Reck and Gpr124 Are Essential Receptor Cofactors for Wnt7a/Wnt7b-Specific Signaling in Mammalian CNS Angiogenesis and Blood-Brain Barrier Regulation

Abstract: Summary Reck, a GPI-anchored membrane protein, and Gpr124, an orphan GPCR, have been implicated in Wnt7a/Wnt7b signaling in the CNS vasculature. We show here that vascular endothelial cell (EC)-specific reduction in Reck impairs CNS angiogenesis and that EC-specific postnatal loss of Reck combined with loss of Norrin impairs blood-brain barrier (BBB) maintenance. The most N-terminal domain of Reck binds to the leucine-rich repeat (LRR) and immunoglobulin (Ig) domains of Gpr124, and weakening this interaction b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
161
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 179 publications
(173 citation statements)
references
References 61 publications
11
161
1
Order By: Relevance
“…Reversion‐inducing cysteine‐rich protein with Kazalmotifs genes are divided into two kinds in vivo, that is, membrane RECK and soluble RECK (Cho, Smallwood, & Nathans, 2017); bothcan be weakly expressed in normal tissues. Studies have shown that post‐transcriptional RECK can inhibit MT1‐MMP.…”
Section: Discussionmentioning
confidence: 99%
“…Reversion‐inducing cysteine‐rich protein with Kazalmotifs genes are divided into two kinds in vivo, that is, membrane RECK and soluble RECK (Cho, Smallwood, & Nathans, 2017); bothcan be weakly expressed in normal tissues. Studies have shown that post‐transcriptional RECK can inhibit MT1‐MMP.…”
Section: Discussionmentioning
confidence: 99%
“…GPR124 exhibits neuronal and non-neuronal expression profiles [8, 9]. GPR124 expression during capillary morphogenesis is induced by the small GTPase Rac and mediates the contact inhibition of proliferation in endothelial cells during angiogenesis [10].…”
Section: Introductionmentioning
confidence: 99%
“…GPR124 functions cell autonomously in the endothelium to regulate sprouting migration, and the developmental expression of the Glucose transporter 1 (Glut1) [8]. Gpr124 was identified as a ligand-specific coactivator of canonical Wnt signaling [13].…”
Section: Introductionmentioning
confidence: 99%
“…Wntdriven vascularization of the CNS is largely mediated by canonical Wnt signaling via the Lrp5/6 receptors and β-catenin transcriptional activity . Transduction of Wnt7a/7b binding to the Frizzled/LRP receptors is achieved through the G-coupled protein receptor, Gpr124 and its co-factor, Reck (C. Cho, Smallwood, & Nathans, 2017;.…”
Section: Cns Vascular Developmentmentioning
confidence: 99%